Taḥdīd Mi‘yār al-Kafā’ah li-al-Ḥadd al-Adná (KKM) li-Māddat al-Lughah al-‘Arabīyah fī al-Madrasah al-Ibtidā’īyah - Ainiy, Nurul; Al-Husna, Alif Saida; Ngarifah, Imroatul; Bahtiyar, Fadhli Hakim; Qomari, Nur (Universitas Negeri Jakarta, 2022)
Defining the Minimum Completeness Criteria (KKM) is the first stage of implementing learning outcome assessment as part of curriculum development. Students are said to succeed in a subject if they achieve the minimum completeness criteria specified in the syllabus. This research aims to study the procedures and the method used to defining the minimum completeness criteria for Arabic lessons at Al-Fattah Elementary School, Batu, Malang. This study used the descriptive-qualitative method. Data collection methods include observation, interviews, and documentation. The results indicate that defining the minimum completeness criteria for Arabic lessons in Al-Fattah Elementary School follows two procedures. First, the Subject Teachers’ Consultation Council (MGMP) defines the minimum completeness criteria at the beginning of the school year, and for each basic competency (KD), its standard is 67, and Arabic language lesson have a standard of 71. Secondly, the minimum completeness criteria that have been defined are published for all Arabic teachers. The process of defining minimum completeness criteria in this school uses the value range method to assign the level of complexity, level of students’ absorption capacity, and efficiency level of auxiliary resources, and then calculates it using the appropriate formula to get the exact score.